Impact of the COVID-19 Pandemic on Mental Health Outcomes of Healthy Children, Children With Special Health Care Needs and Their Caregivers-Results of a Cross-Sectional Study - Anne Geweniger; Michael Barth; Anneke D. Haddad; Henriette Högl; Shrabon Insan; Annette Mund; Thorsten Langer (Frontiers Media S.A., 2022)
BackgroundSeveral studies have described widening inequalities as a result of the COVID-19 pandemic, mostly for adult populations. Children and adolescents are particularly impacted by the indirect effects of the pandemic and lockdown measures, such as reduced access to or delays in health care and school closures. National surveys in several countries also show a rising mental health burden in children and adolescents during the COVID-19 pandemic. Children with special health care needs are a particularly vulnerable group in this context as they rely on a wide range of services, which were mostly suspended during the first wave of the pandemic. This study aims: (1) to describe the mental health outcomes of children with and without special healthcare needs and of their caregivers following the first national lockdown in Germany; (2) to investigate variations in mental health outcomes and measures of pandemic burden according to socioeconomic status; (3) to assess the impact of socioeconomic status, disease complexity and psychosocial burden on parent-reported child mental health problems.MethodsWe conducted an online survey among 1,619 caregivers of children aged 1-18 years from August 11th until October 5th 2020. Participants were recruited both from families of children with special healthcare needs and of healthy children. Inequalities were analysed by descriptive statistics, simple and hierarchical logistic regression modelling to explore the association between socioeconomic status and psychological outcome measures, disease complexity and general burden related to COVID-19.ResultsThere was a high prevalence of 57.4% of parent-reported mental health problems in children and of a positive screening score for depression in 30.9% of parents. Parent-reported mental health problems were more likely to affect children with low socioeconomic status, with complex chronic disease and those whose parents screened positive for depression.ConclusionsThis study highlights inequalities in parent-reported child mental health outcomes by socioeconomic status and disease complexity in a large sample of German families with and without children with special health care needs. Political measures should put children at the centre and aim to mitigate the unequal impact of the COVID-19 pandemic, particularly on the mental health of vulnerable children.